Mitochondria dysfunction and bipolar disorder: from pathology to therapy - Lam, Xin-Jieh; Xu, Bingzhe; Yeo, Pei-Ling; Cheah, Pike-See; Ling, King-Hwa (Elsevier, 2023)
Bipolar disorder (BD) is one of the major psychiatric diseases in which the impairment of mitochondrial functions has been closely connected or associated with the disease pathologies. Different lines of evidence of the close connection between mitochondria dysfunction and BD were discussed with a particular focus on (1) dysregulation of energy metabolism, (2) effect of genetic variants, (3) oxidative stress, cell death and apoptosis, (4) dysregulated calcium homeostasis and electrophysiology, and (5) current as well as potential treatments targeting at restoring mitochondrial functions. Currently, pharmacological interventions generally provide limited efficacy in preventing relapses or recovery from mania or depression episodes. Thus, understanding mitochondrial pathology in BD will lead to novel agents targeting mitochondrial dysfunction and formulating new effective therapy for BD.